Antibodies to colonic epithelial cells from the serum and colonic mucosal washings in ulcerative colitis. (July 1995) - Khoo, U Y; Bjarnason, I; Donaghy, A; Williams, R; Macpherson, A
Abstract : It has been suggested that antibodies to a colonocyte protein of 40 kD (an intestinal isoform of tropomyosin) are specifically found in the serum and mucosa of patients with ulcerative colitis, which has important pathogenic implications. This study isolated and purified tropomyosin from the colonic mucosa, but no specific binding to this protein has been detected in serum samples or immunoglobulins isolated from mucosal washings of 20 ulcerative colitis (UC) patients by enzyme linked immunosorbent assay (ELISA) compared with 21 controls or 17 Crohn's disease (CD) patients. Samples from a further 12 patients with UC and primary sclerosing cholangitis (it is proposed that cross reactivity against the intestinal tropomyosin isoform accounts for the extraintestinal disease) also did not show binding to tropomyosin, whereas monoclonal antitropomyosin antisera bound both ELISAs and western blots. This study also examined the proteins in the normal colonic biopsy specimens on western blots that are bound by both serum samples and mucosal immunoglobulin preparations from these patients groups; there was no specific IgG or IgA binding to patients with UC or UC/primary sclerosing cholangitis, whereas binding to mitochondrial proteins of 70, 000 and 45, 000 was seen in samples from 12 primary biliary cirrhosis positive controls. This work does not support the hypothesis that autoimmune activity against the intestinal isoform or tropomyosin is important in the pathogenesis of ulcerative colitis.